Geographical discrimination and authentication of Chinese garlic based on multi-element, volatile and metabolomics profiling combined with chemometrics. (December 2021) - Mi, Si; Zhang, Xiangnan; Wang, Yuhang; Yan, Fulong; Sang, Yaxin; Gong, Heyou; Wang, Xianghong
Abstract: This study aims to discriminate the garlics collected from four different geographical locations of China. The multi-element (12 samples), volatile (12 samples) and metabolome (24 samples) composition of the garlics were analyzed and compared. A total of 34 chemical elements, 68 volatiles and 854 metabolites were detected in the garlic samples. Significant differences were observed in the chemical element, volatile and metabolomics profiles of the four groups of garlic. Multivariate statistics indicate that 10 chemical elements, 6 volatiles and 225 metabolites could be used as candidate markers for the separation of garlics obtained from Langfang, Jining, Kaifeng and Dali of China. The current work provides a chemical fingerprint of the selected Chinese garlics. Our results demonstrate that chemical profiling in combination with chemometrics has the potential to be used as feasible approaches for the authentication of the geographical origin of garlic. Graphical abstract: Image 1 Highlights: Garlic from four Chinese territories were analyzed and discriminated. A total of 55 chemical elements were quantified in the garlic samples using ICP-MS. A total of 68 volatiles were identified in the garlic samples by HS-SPME-GC-MS. A panel of 854 metabolites were putatively annotated in garlic by UHPLC-Q-TOF/MS. Garlics were separated based on the elemental, volatile and metabolomics profiles.